Rumah Baca Sebagai Media Literasi Anak Di Desa Pulau Telo Baru Kecamatan Selat Kabupaten Kapuas - Pratama, Oklan; Hamidah, Noor; Lumbanraja, Aprilia Junika; Rahman, Rahman; Rahmah, Umi; Nagita, Nagita; Ratnasari, Elda; Sitohang, Malemahaetma; Fernanda, Enjelika; Viana, Wanda; Gloria, Debora; Antaraeni, Mira; Prasetyo, Agung; Mariffah, Mariffah; Afrizal, Mohammad; Jesica, Agnes (Fakultas Teknik Universitas Palangka Raya, 2024)
Literacy is an individual skill in absorbing knowledge. Most of the educational process depends on literacy skills and awareness. The literacy culture embedded in students affects their level of success, both at school and in community life. The purpose of this community service activity is to provide assistance to village communities in realizing a reading house in Pulau Telo Baru Village, Selat District, Kapuas Regency. The method of the activity is assistance with a qualitative approach from information sources in the form of interviews with the village head and the principal of SDN 1 Pulau Telo Baru regarding the unavailability of a reading house in Pulau Telo Baru Village. The results of this community service have proven to be able to reduce the problem of reading difficulties, provide space to develop literacy interests, the urgent need for a reading room and initiate a Reading House.